Hoarding revisited: there is light at the end of the living room. (8th November 2018) - Pertusa, Alberto; Lopez Gaston, Romina; Choudry, Abid
SUMMARY: Since 2013, hoarding disorder has been recognised as a standalone diagnosis in the DSM, affecting an estimated 2–6% of the general population. This article outlines the arguments for and against this separate classification and considers the differentiation of hoarding disorder from normative collecting. It then discusses aetiology, assessment, course and treatment (both psychological and pharmacological interventions). It concludes with a discussion of ethical and legal considerations, in particular the fact that the inclusion of hoarding disorder as a distinct diagnosis in DSM-5 confers specific protections for people with the disorder under the Equality Act 2010. LEARNING OBJECTIVES: Be able to define the criteria of hoarding disorder Be able to recognise the difference between hoarding and collecting Understand potential treatment options for patients with hoarding disorder DECLARATION OF INTEREST: None.